Behaviours of rip cosmological models in f(Q,C) gravity - Amit Samaddar; S. Surendra Singh; Shah Muhammad; Euaggelos E. Zotos (Nuclear Physics B, 2024)
In this study, the Universe's rip cosmology theories have been provided for the f(Q,C) gravity theory, where Q and C stand for the non-metricity scalar and boundary term. We assume f(Q,C)=αQn+βC and analyze the nature of the physical parameters for the Little Rip (LR), Big Rip (BR) and Pseudo Rip (PR) models. In the LR and PR models, the EoS parameter exhibits phantom characteristics but remains closely aligned with the ΛCDM line. The non-metricity term Q has direct effect on the rip models. After investigating the energy conditions, we recognise that our model violates the strong energy constraint. Avoiding singularity situations has been noted in all of these accelerated models. The characteristics of the jerk and snap parameters have been investigated. Our model provides an effective description of the Universe's evolutionary history and fits well with contemporary cosmic data.